COVID-19 and Teachers' Somatic Burden, Stress, and Emotional Exhaustion: Examining the Role of Principal Leadership and Workplace Buoyancy - Rebecca J. Collie (SAGE Publishing, 2021)
The role of two leadership factors (autonomy-supportive and autonomy-thwarting leadership) and one personal resource (workplace buoyancy) were examined as predictors of three teacher outcomes: somatic burden, stress related to change, and emotional exhaustion. Data were collected from 325 Australian teachers in May, 2020 during the first wave of COVID-19. During this time, many Australian children were being taught remotely from home, while other students were attending schools in-person. Findings showed that autonomy-supportive leadership was associated with greater buoyancy and, in turn, lower somatic burden, stress related to change, and emotional exhaustion (while controlling for covariates, including COVID-19 work situation). Autonomy-thwarting leadership was positively associated with emotional exhaustion. In addition, autonomy-supportive leadership was indirectly associated with the outcomes. The findings provide understanding of factors that may be harnessed to support teachers during subsequent waves of COVID-19 and other future disruptions to schooling that may occur.